Colorectal Cancer Cells–Derived Exosomal PIK3CA Mutation DNA Promotes Tumor Metastasis by Activating Fibroblast and Affecting Tumor Metastatic Microenvironment - Rui Wang; Wanming Li; Yuqiong Lv; Wei Ba; Ying Jiang; Xiaoshuai Li; Jin Fang (Advanced Science)
Abstract Exosomes participate in the formation of the tumor metastatic microenvironment (TME) by delivering tumor‐specific substances. However, current studies mostly focus on exosomal RNA and proteins and lack an in‐depth exploration of exosomal DNA. It is discovered that PIK3CAH1047R mutant DNA in colorectal cancer (CRC) cell‐derived exosomes can be delivered into recipient fibroblasts, where they are transcribed and translated, ultimately leading to the activation of fibroblasts into cancer‐associated fibroblasts (CAFs) through interaction with the endogenous P85 regulatory subunit of the phosphatidylinositol 3‐kinase (PI3K) pathway. CAFs have facilitated tumor cell migration in vitro and promote lung metastasis in vivo by secreting elevated levels of IL6. Additionally, the PIK3CAH1047R mutation is detected in CAFs at both the primary and metastatic sites, suggesting that it may play a role in promoting metastasis by influencing the TME. Moreover, patients with CRC harboring the PIK3CAH1047R mutation and exhibiting elevated levels of IL6 are significantly more likely to metastasize. These findings suggest that the simultaneous detection of serum‐derived exosomal PIK3CAH1047R mutation and serum IL6 secretion may serve as a promising diagnostic and prognostic tool for CRC and simultaneous targeting of PIK3CAH1047R mutation and IL6 may serve as a novel approach for the treatment of CRC.